Degradasi Hutan dan Pengangguran: Menuju Pengelolaan Hutan Skala Kecil (Forest Degradation and Unemployment: Towards Small-scale Forest Management) - Herry Purnomo (Institut Pertanian Bogor (IPB University), 2006)
Along with the concept of poverty alleviation and forest sustainability, forestry employment is the major concern among policy makers. The forest sustainability and job availability are critical indicators for the performance of the government. The relationship between employment and forestry development is unclear especially when it deals with illegal forestry activities. This study aims at generating projection of the forestry employment in Indonesia in relation to the dynamic of forestry sector and its related industries,. The study used systems dynamic to implement the relation between forest structure industries, actors and their institutions. The study found that the current practice of forest management will experience with boom-and-bust of forestry employment, starting with Riau followed by East Kalimantan and Papua. Massive forest plantingwill benefit if it is located in deforested land, but if it is located in land with different existing trees it may jeopardize the employment and community’s livelihoods. Small-scale forestry can boost the employment to meet the overall government target on unemployment and poverty reduction as well as rehabilitation of forest.Keywords: forest degradation, unemployment, land-right scenarios, small-scale forestry, poverty-reduction